2020
DOI: 10.3390/v12090921
|View full text |Cite
|
Sign up to set email alerts
|

Employing Molecular Phylodynamic Methods to Identify and Forecast HIV Transmission Clusters in Public Health Settings: A Qualitative Study

Abstract: Molecular HIV surveillance is a promising public health strategy for curbing the HIV epidemic. Clustering technologies used by health departments to date are limited in their ability to infer/forecast cluster growth trajectories. Resolution of the spatiotemporal dynamics of clusters, through phylodynamic and phylogeographic modelling, is one potential strategy to develop a forecasting tool; however, the projected utility of this approach needs assessment. Prior to incorporating novel phylodynamic-based molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…In this study, we reconstructed and analyzed transmission networks of CRF01_AE, the most prevalent recombinant form of HIV-1 in Bulgaria, by combining traditional epidemiological data with HIV-1 pol sequences collected through 2019 and conducting phylogenetic and network analyses. Our phylodynamic approach has been used successfully before for the subtype B sub-epidemic in Bulgarian [ 30 ] and these methods are becoming standard analyses for cluster and outbreak investigations for HIV prevention [ 31 , 32 , 33 , 34 ]. We found that CRF01_AE infections grew into a large sub-epidemic among PWID, after it was first introduced into Bulgaria, most likely from Vietnam, with some onward transmission to other European countries.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we reconstructed and analyzed transmission networks of CRF01_AE, the most prevalent recombinant form of HIV-1 in Bulgaria, by combining traditional epidemiological data with HIV-1 pol sequences collected through 2019 and conducting phylogenetic and network analyses. Our phylodynamic approach has been used successfully before for the subtype B sub-epidemic in Bulgarian [ 30 ] and these methods are becoming standard analyses for cluster and outbreak investigations for HIV prevention [ 31 , 32 , 33 , 34 ]. We found that CRF01_AE infections grew into a large sub-epidemic among PWID, after it was first introduced into Bulgaria, most likely from Vietnam, with some onward transmission to other European countries.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, population displacement may be re ected in the treatment of HIV-infected individuals as patients who had to relocate because of the con ict may be more likely to reduce treatment adherence. Hence then the spread of HIV-1 strains is becoming a serious public health challenge that requires further studies to understand deeply their origin and distribution (29). Different comments should be raised concerning the limitations of this study.…”
Section: Discussionmentioning
confidence: 93%
“…Last, we assessed variation in relative transmission dynamics among individual clades as well as local Florida sub-trees within each clade in the context of mutational patterns. For each cluster, we calculated the Oster statistic, which is a function of the size in tips, the sum of the branch lengths, and the length of the longest branch within an individual subtree [45,46]. This method was recently developed to infer transmission rates using human immunodeficiency virus (HIV) sequencing data.…”
Section: Methodsmentioning
confidence: 99%